Some Weak Variants of the Existence and Disjunction Properties in Intermediate Predicate Logics - Suzuki, Nobu-Yuki (Bulletin of the Section of Logic, 2017)
We discuss relationships among the existence property, the disjunction property, and their weak variants in the setting of intermediate predicate logics. We deal with the weak and sentential existence properties, and the Z-normality, which is a weak variant of the disjunction property. These weak variants were presented in the author’s previous paper [16]. In the present paper, the Kripke sheaf semantics is used.